Wacode “Wates Coco Delight” & VCO “Virgin Coconut Oil”: Innovation Coconut Products - Nindyawati, Eliza; Salsabila, Rizki Kurnia; Siswahyudi, Jodi; Puspitasari, Ririn Dwi; Putri, Devi Kartika; Mashudi, Sugeng (CV. BImbingan Belajar Assyfa, 2024)
As an ecotourism village, Wates needs to take strategic steps to maximize its potential and attractions and maintain environmental sustainability. One way is to empower local communities through ecotourism management training and how to maximize the potential of coconut as a superior village product. This study aims to identify and develop the potential of coconut in Wates Village into creative and economical products, namely